Endovascular therapy versus femoropopliteal bypass surgery for medium-length TASC II B and C lesions of the superficial femoral artery: An observational propensity-matched analysis. (October 2019) - Vossen, RJ; Vahl, AC; Fokkema, TM; Leijdekkers, VJ; van Swijndregt, AD Montauban; Balm, R
Objectives: This study was designed to compare clinical outcomes of percutaneous transluminal angioplasty with optional stenting (PTA/s) and femoropopliteal bypass (FPB) surgery as primary invasive treatment in patients with medium-length superficial femoral artery (SFA) lesions. Methods: We performed a single-center retrospective, observational analysis in all consecutive patients who had undergone initial invasive treatment for medium-length, TASC II B and TASC II C, SFA lesions from 2004 to 2015. Primary endpoints were primary and secondary clinical patency. Secondary endpoints were complication rates and number of amputations. Kaplan–Meier curves were used to compare patency rates in the two treatment groups. Multivariate Cox regression analysis was performed to adjust for confounding variables and propensity score matching analysis was used to balance treatment groups. Results: A total of 362 patients with a mean observation period of 4.0 years (SD ± 2.6) were analyzed. In this group, 231 patients (64%) underwent PTA/s and 131 patients (36%) FPB surgery. There was no difference in primary clinical patency at one-, three- and five-year follow-up between the PTA/s and FPB group, with rates of 79% vs. 63%, 53% vs. 78% and 71% vs. 66%, respectively ( P = 0.46). Secondary clinical patency estimates were comparable, resulting in one-, three- and five-year secondary clinical patency rates of 88%, 76% and 67% in the PTA/s group versus 88%, 80% and 79% in the bypass group ( P = 0.40). Multivariate analysis revealed no significant differences between the PTA/s and FPB groups in terms of primary clinical patency (HR 1.4; 95% CI 0.9–2.2) and secondary clinical patency (HR 1.7; 95% CI 0.9–2.9). This was confirmed in the propensity score analysis. Hospital stay (4.8 vs. 10.3 days) and complication rate (2.6% vs. 18.3%) were significantly lower in the PTA/s group ( P = 0.00). The number of amputations was comparable ( P = 0.75). Conclusions: The clinical success of endovascular therapy and surgery for medium-length SFA lesions is comparable. Taking into account the lower morbidity rate, shorter length of hospital stay and the less invasive character of PTA/s compared with bypass surgery, patients with medium-length SFA lesions are ideally treated by an endovascular-first approach.